2022
DOI: 10.3389/fneur.2022.928070
|View full text |Cite
|
Sign up to set email alerts
|

A Comparation Between Frame-Based and Robot-Assisted in Stereotactic Biopsy

Abstract: IntroductionFrame-based stereotactic biopsy is well-established to play an essential role in neurosurgery. In recent years, different robotic devices have been introduced in neurosurgery centers. This study aimed to compare the SINO surgical robot-assisted frameless brain biopsy with standard frame-based stereotactic biopsy in terms of efficacy, accuracy and complications.MethodsA retrospective analysis was performed on 151 consecutive patients who underwent stereotactic biopsy at Chongqing Sanbo Jiangling Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(69 reference statements)
0
5
1
Order By: Relevance
“…compared 47 patients with traditional frame brain biopsy and 104 patients with Sinovation SR1 robot-assisted brain biopsy, and made statistical analysis on the efficacy, accuracy and complications of the biopsy. 42 The results showed that there was no significant difference in the diagnostic rate between the frame-based group and the Sinovation SR1 robot-assisted group (95.74% vs. 98.08%, p > 0.05). The mean operation time of the Sinovation SR1 robot-assisted group was significantly shorter than that of the frame-based group (29.36 ± 13.64 vs. 50.57 ± 41.08 min, p < 0.01).…”
Section: Clinical Applicationmentioning
confidence: 84%
See 1 more Smart Citation
“…compared 47 patients with traditional frame brain biopsy and 104 patients with Sinovation SR1 robot-assisted brain biopsy, and made statistical analysis on the efficacy, accuracy and complications of the biopsy. 42 The results showed that there was no significant difference in the diagnostic rate between the frame-based group and the Sinovation SR1 robot-assisted group (95.74% vs. 98.08%, p > 0.05). The mean operation time of the Sinovation SR1 robot-assisted group was significantly shorter than that of the frame-based group (29.36 ± 13.64 vs. 50.57 ± 41.08 min, p < 0.01).…”
Section: Clinical Applicationmentioning
confidence: 84%
“…41 Sinovation SR1 1.4 (0.4–9.3) >0.05 8.0 (5.9–12.8) <0.01 Frame 1.4 (0.0–4.6) 14.7 (10.3–18.5) Biopsy Hu et al. 42 Sinovation SR1 1.10 ± 0.30 (0.69–2.03) <0.05 29.36 ± 13.64min <0.05 Frame 1.63 ± 0.41 (0.74–2.65) 50.57 ± 41.08 min Wu et al. 43 Remebot 80.1 ± 12.3 <0.01 Frame 116.5 ± 14.1 …”
Section: Clinical Applicationmentioning
confidence: 99%
“…Remebot robot-assisted frameless brain biopsy is easy to use and better accepted by patients than frame-based biopsy. Frameless biopsy is associated with shorter procedural times relative to frame-based biopsy, and it may have wider indications in brain biopsy due to its high flexibility [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study was that they compared two frameless robotic and image-guided surgery systems to prove the efficiency and safety of robotic surgery without a frame-based control group. In another study, Hu et al compared the SINO (Sinovation Medical Technology Co., Ltd., Beijing, China) surgical robot-assisted frameless brain biopsy with standard frame-based stereotactic biopsy in terms of efficacy, accuracy, and complications [ 22 ]. Although there was no significant difference in diagnostic yield and postbiopsy complications between the frame-based group and the SINO robot-assisted group, the entry and target point errors were smaller in the robot-assisted group.…”
Section: Innovations To Improve Perioperative Workflowmentioning
confidence: 99%